Oral lactoferrin administration does not impact the diversity or composition of the infant gut microbiota in a Peruvian cohort - Luis González; Jose Luis Paredes Sosa; Susan Mosquito; Yesenia Filio; Pedro E. Romero; Theresa J. Ochoa; Pablo Tsukayama (Microbiology Spectrum, 2023)
ABSTRACT Lactoferrin is a protein from breast milk involved in early-life microbiome assembly. It is believed to promote the growth of lactic acid-producing bacteria and inhibit pathogens by limiting iron availability and enabling an acidic environment in the gut. Previous reports suggest that oral administration of lactoferrin in neonates promotes the increase of gut microbiota diversity and the enrichment of beneficial microbes. However, its effect on infant gut microbiota over time has yet to be thoroughly studied to fully understand its potential as a prebiotic. Using 16s rRNA gene amplicon sequencing, we analyzed the gut microbiota composition of 60 toddlers at 12–18 months of age from Lima, Peru, who received daily oral administration of lactoferrin or placebo for 6 months since enrollment. Samples were analyzed at 0, 2, and 4 months after beginning treatment. Our results show that lactoferrin treatment does not increase gut microbiota diversity over time nor affect its bacterial composition compared to the placebo group. IMPORTANCE Previous studies have suggested that oral lactoferrin enhances diversity in the gut microbiota in infants while inhibiting the growth of opportunistic pathogens. However, the effect of lactoferrin on infant gut microbiota over time has yet to be thoroughly studied. Our study suggests that lactoferrin oral treatment in infants aged 12–18 months does not affect gut microbiome diversity and composition over time. To our knowledge, this is the first study to report the effect of lactoferrin on infant gut microbiome composition over time and helps elucidate its impact on infant health and its therapeutic potential.